Single wheel hub motor failures and their impact on vehicle and driver behaviour. Issue 10 (2nd October 2016) - Wanner, Daniel; Kreußlein, Maria; Augusto, Bruno; Drugge, Lars; Stensson Trigell, Annika
ABSTRACT: This research work studies the impact of single wheel hub motor failures on the dynamic behaviour of electric vehicles and the corresponding driver reactions. An experimental study in a moving-base driving simulator is conducted to analyse the influence of single wheel hub motor failures for motorway speeds. Driver reaction times are derived from the measured data and discussed in their experimental context. The failure is rated objectively on the dynamic behaviour of the vehicle and compared to the subjective evaluation. Findings indicate that critical traffic situations impairing traffic safety can occur for motorway speeds. Clear counteractions by the drivers had to be taken.